Tingkat Pengetahuan Bantuan Hidup Dasar Mahasiswa Profesi Fakultas Kedokteran Universitas Udayana - Palaguna, I Dewa Gde Bagus Panji; Ariastuti, Ni Luh Putu; Widyanthini, Desak Nyoman (E-Jurnal Medika Udayana; Vol 13 No 4 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i04.P06, 2024)
The level of knowledge of basic life support affects the rate of CPR in out-of-hospital cardiac arrest. It plays a role in increasing the survival rate of out-of-hospital cardiac arrest patients. This cross-sectional descriptive study used an online survey with 20 questions related to basic life support. Respondents' answers were processed into good knowledge level (score 76-100%), sufficient (score 56-75%), and less (score <56%), then divided based on the characteristics of the sample and described in narrative form. From a total of 86 respondents, it was found that the characteristics of the study program were 52 (60.5%) medical students, 34 (39.5%) nursing students aged 21-24 years and had experience participating in BLS training, but only 9 (10, 5%) who have experience providing BLS actions. A total of 33 (38.4%) have good knowledge, 43 (50%) have sufficient knowledge, and 10 (11.6%) have poor knowledge. Twenty-nine out of 52 medical student respondents had good knowledge, and 21 out of 34 nursing student respondents had sufficient knowledge. Most respondents with experience doing BLS have good knowledge and sufficient knowledge of respondents who do not have experience of doing so.